Household Waste Separation and 3R Practice: Comparison Between the Urban and Rural Communities in Ipoh, Perak - Heo, Ruoh Jau; Ali, Roslinda (Progress in Engineering Application and Technology, 2024)
Solid waste management is a global concern that presents a significant challenge to every nation when it comes to environmental deterioration. Malaysia is one of the countries grappling with challenges in solid waste management due to the substantial generation of waste and the waste disposal practiced over the years. This research intends to investigate the household waste separation and 3R practice of urban and rural communities in Ipoh, Perak. Tambun and Menglembu are chosen as the urban and the rural research areas respectively. A questionnaire survey was distributed to the residents who stayed in these areas. A total of 202 questionnaires were returned and the data was analysed by using the Package for Social Science (SPSS) software. The analysis carried out includes descriptive statistics, cross-tabulation analysis, and correlation tests. The findings revealed that there is a correlation between residential areas and 3R practice. Urban and rural communities have moderate awareness levels and knowledge concerning 3R, although rural communities still lag behind urban communities. However, the results indicated that urban communities tend to practice waste separation and 3R better in contrast to the rural communities. In addition, the availability of 3R facilities contributes to the tendency to practice waste separation and 3R among urban communities and difficulty in engaging in 3R practices among rural communities. Overall, it can be concluded that the objectives of this research have been successfully achieved.